Thermal Imaging of Root Caries In Vivo. (December 2020) - Yang, V.; Zhu, Y.; Curtis, D.; Le, O.; Chang, N.Y.N.; Fried, W.A.; Simon, J.C.; Banan, P.; Darling, C.L.; Fried, D.
Improved methods are needed to assess the structure and activity of lesions on root surfaces in order to improve clinical decision making. Conventional visual and tactile methods for assessing lesion activity are not reliable, and the clinician is often unable to evaluate if the lesion is progressing or has remineralized. An important marker of an arrested lesion is a highly mineralized surface zone that forms when mineral is deposited in the outer layer of the lesion. In vitro studies have shown that a mineralized surface zone influences the kinetics of water evaporation and the surface temperature while drying. Temperature changes can be monitored by measuring the thermal emission with thermal imaging. Studies have also shown that the depth and severity of demineralization and the thickness of the highly mineralized transparent surface zone on arrested lesions can be measured nondestructively with optical coherence tomography (OCT). Thermal imaging at 8-µm to 13-µm wavelengths was completed on 30 test subjects with a suspected active root caries lesion by monitoring thermal emission from the tooth surfaces during 30 s of air drying. Lesions were also evaluated using cross-polarization OCT (CP-OCT) during lesion dehydration to identify transparent surface zones indicative of arrested lesions and determine if shrinkage occurred during drying. The overall thermal emission recorded during drying was significantly different ( P < 0.001) when comparing sound tooth surfaces, lesion areas identified as arrested, and lesion areas identified as active, demonstrating that thermal imaging is a promising approach for the clinical assessment of lesion activity on root surfaces. Ten of the lesions in this study had distinct areas with transparent surface zones that were visible in CP-OCT images. Shrinkage was detected with CP-OCT during drying for 12 lesions. This study confirms that these novel approaches for assessing lesion activity on root surfaces can be implemented in vivo.